2014
DOI: 10.1371/journal.pone.0108455
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Potential of Selegiline in Attenuating Organ Dysfunction in Septic Rats with Peritonitis

Abstract: Selegiline, an anti-Parkinson drug, has antioxidant and anti-apoptotic effects. To explore the effect of selegiline on sepsis, we used a clinically relevant animal model of polymicrobial sepsis. Cecal ligation and puncture (CLP) or sham operation was performed in male rats under anesthesia. Three hours after surgery, animals were randomized to receive intravenously selegiline (3 mg/kg) or an equivalent volume of saline. The administration of CLP rats with selegiline (i) increased arterial blood pressure and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Widely used in the treatment of Parkinson's disease [10], selegiline is an irreversible inhibitor with selectivity for monoamine oxidase type B (MAO-B) that in recent studies showed anti-inflammatory and anti-apoptotic properties [11]. It has been shown to reduce total brain damage after transient hypoxiaischaemia, to maintain mitochondrial membrane potential, and to eliminate oxygen radicals [12].…”
Section: Introductionmentioning
confidence: 99%
“…Widely used in the treatment of Parkinson's disease [10], selegiline is an irreversible inhibitor with selectivity for monoamine oxidase type B (MAO-B) that in recent studies showed anti-inflammatory and anti-apoptotic properties [11]. It has been shown to reduce total brain damage after transient hypoxiaischaemia, to maintain mitochondrial membrane potential, and to eliminate oxygen radicals [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that selegiline prevents ROS production and lipid peroxidation . A research by Tsao and colleagues revealed that selegiline is a potential adjuvant therapy for the treatment of sepsis by attenuating the oxidative and nitrosative stress, decreasing acidosis and inflammation, and rescuing organ failure including heart failure …”
Section: Discussionmentioning
confidence: 99%
“…Also, our histopathological results in cardiac tissue suggest that selegiline at lower doses (1, 5 mg/kg) prevents the infiltration of lymphocyte into interstitium. Moreover, other reports showed that selegiline reduced neutrophil infiltration into the liver and lung in an animal model of caecal ligation and puncture‐induced sepsis . Inhibition of acetylcholinesterase (ACE) in the brain is one of the mechanisms through which AlP exerts its toxic effects .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a selective MAO-B inhibitor, selegiline may be used as an anti-PD drug to exert antioxidant and anti-apoptotic effects (29,30). It has also been indicated that selegiline decreases oxidative stress and cell death induced by 1-methyl-4-phenylpyridinium (MPP + ), an inducing agent of PD (31).…”
Section: Discussionmentioning
confidence: 99%